Direct cost of monitoring conventional hemodialysis conducted by nursing professionals - Lima,Antônio Fernandes Costa (2017)
ABSTRACT Objective: to analyze the mean direct cost of conventional hemodialysis monitored by nursing professionals in three public teaching and research hospitals in the state of São Paulo, Brazil. Method: this was a quantitative, explorative and descriptive investigation, based on a multiple case study approach. The mean direct cost was calculated by multiplying (clocked) time spent per procedure by the unit cost of direct labor. Values were calculated in Brazilian real (BRL). Results: Hospital C presented the highest mean direct cost (BRL 184.52), 5.23 times greater than the value for Hospital A (BRL 35.29) and 3.91 times greater than Hospital B (BRL 47.22). Conclusion: the costing method used in this study can be reproduced at other dialysis centers to inform strategies aimed at efficient allocation of necessary human resources to successfully monitor conventional hemodialysis.